Correlation between CK18 gene and gastric carcinoma micrometastasis - Xu, Wei (World J Gastroenterol, 2005)
AIM: To explore the biological behavior of gastric carcinoma micrometastasis (MM) with a marker of cytokeratin 18 (CK18) and to evaluate the clinical stage of gastric carcinoma and its prognosis. METHODS: Reverse transcription-polymerase chain reaction (RT-PCR) was used to examine the expression of CK18 mRNA in 298 lymph nodes from 35 patients with gastric carcinoma and 20 lymph nodes from 10 patients with chronic peptic ulcer and gastric perforation diagnosed by pathological examination and surgery. CK18 mRNA expression of peripheral blood from 54 patients with gastric carcinoma and 10 healthy people were also examined. RESULTS: Expression of CK18 mRNA was not found in 10 patients with benign pathological changes. CK18 mRNA expression in gastric carcinoma tissues was strongly positive. In gastric carcinoma patients, pathological examination revealed that 99 of 298 (33.2%) lymph nodes were positive, while RT-PCR showed that 133 of 298 (44.6%) lymph nodes had expression of CK18 mRNA. The difference was significant (P < 0.05). Among the 199 negative lymph nodes identified by pathological examinations, 34 (17.1%) displayed positive expression of CK18 mRNA by RT-PCR. The positive expression of CK18 mRNA was associated with lymph node micrometastasis (LMM) of gastric carcinoma. CK18 mRNA was negatively expressed in all 10 healthy cases and positively expressed in 38.9% of 54 blood specimens from gastric carcinoma patients. The positive rate was not correlated with tumor invasion of gastric carcinoma, but was significantly associated with TNM stage, lymph node metastasis (P = 0.0290, P < 0.05) and tumor differentiation (P = 0.2956, P<0.05). CONCLUSION: RT-PCR with CK18 mRNA as a molecular marker is highly sensitive and specific in detecting LMM of gastric carcinoma. It can benefit the diagnosis of MM and guide studies on biological behavior, clinical phase, and therapy as well as relapse monitoring.